Pathologies of Love : Medicine and the Woman Question in Early Modern France - Kem, Judy (Book collections on Project MUSE., 2019)
"Judy Kem looks at the writings of Christine de Pizan, Jean Molinet, Symphorien Champier, Jean Lemaire de Belges, and Marguerite de Navarre, examining the role of received medical ideas in the Querelle des femmes"--